Proceso de atención de enfermería a paciente de 38 años de edad con miomatosis uterina. - Bajaña Rivera Elena Jacinta (2020)
Uterine fibroids or leiomyomas are solid benign tumors, which develop in the smooth muscle of the uterus, their shape, size and location is variant. Depending on its location, it is classified as submucosal, intramural and subserosal, they can affect women between 25 and 50 years of age, in Ecuador its incidence comprises 30 or 50% of women affected by this pathology. In the development of this clinical case, we will treat a 38-year-old patient with a clinical picture of severe abdominal pelvic pain plus vaginal bleeding for more than 48 hours of evolution, for this reason she was admitted to the hospital area, performing complementary tests. to diagnose uterine myomatosis, since this pathology causes deterioration of both physical and emotional output. The general objective that I set for myself is to apply the nursing care process to a 38-year-old patient with uterine fibroids to restore their real and potential problems that are evident during the evaluation.